The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15386/cjmed-1030
|View full text |Cite
|
Sign up to set email alerts
|

Kimura Disease : Case Report and Brief Review of Literature

Abstract: Kimura disease is a rare chronic inflammatory disorder of unknown cause, primarily seen in young Asian males. The disease is characterized by painless subcutaneous swelling, blood and tissue eosinophilia and raised IgE levels. Early diagnosis of Kimura’s disease may spare the patient from unnecessary invasive diagnostic procedure. We describe a case of Kimura disease in a 14-year old male presenting with left submandibular swelling and also provide a brief review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 11 publications
(26 reference statements)
1
47
1
Order By: Relevance
“…Kimura disease is a rare chronic inflammatory disease of unknown origin, first described by Kimura et al in 1948 1 . To date, there have only been 200 reported incidences of Kimura disease globally, 2 and only 1 reported case of Kimura Disease of the Breast in 2016 3 . Kimura disease predominantly occurs in Asian male populations, with incidence peaking around the second and third decade of life 4,5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimura disease is a rare chronic inflammatory disease of unknown origin, first described by Kimura et al in 1948 1 . To date, there have only been 200 reported incidences of Kimura disease globally, 2 and only 1 reported case of Kimura Disease of the Breast in 2016 3 . Kimura disease predominantly occurs in Asian male populations, with incidence peaking around the second and third decade of life 4,5 …”
Section: Discussionmentioning
confidence: 99%
“…Patients commonly present with a palpable unilateral lump in their head and neck region including the salivary glands, but other regions including the axilla, groin, and arm have also been reported 2,4 . About 10 to 60% of patients with Kimura disease suffer from concurrent nephrotic syndrome, 5 with biopsies showing a membranous glomerulonephritis and mesangial proliferation, eosinophilic interstitial infiltrates, and some podocytic foot process effacement 9…”
Section: Discussionmentioning
confidence: 99%
“…It is often accompanied by peripheral eosinophilia and markedly elevated serum IgE levels. 10 Although eosinophilia and increased IgE, tumors necrosis factor-alpha, interleukin IL-4, IL 5, IL-13, and mast cell levels in peripheral blood, as well as in the lesion, were observed in these patients, no specific antigens have been identified. 11 It has been proposed that autoimmunity, allergy, neoplasm's, and parasite infestation are possible risk factors.…”
Section: Discussionmentioning
confidence: 82%
“…Some authors were able to diagnose Kimura’s disease on FNAC [ 13 ], whereas others have reported the swellings as lymphadenitis or malignancies [ 14 , 15 ]. The characteristic features of Kimura’s disease on FNAC are the presence of significant numbers of eosinophils in a background of lymphoid cells, with fragments of collagenous tissue, endothelial cells and occasional polykaryocytes [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%